Aegean art and architecture - Preziosi, Donald, 1941-; Hitchcock, Louise; Oxford University Press (Oxford ; New York : Oxford University Press, 1999)
"This is an introduction to the art and architecture of mainland Greece, Crete, and the Cycladic Islands from 3300 to 1000 BCE. Ancient Aegean culture has a particularly important place within European history and art history because of its profound links to the origins of European civilization." "Paintings, pottery, objects made from gold, silver, and ivory, carved reliefs, textiles, and architecture, are fully illustrated and discussed. The authors reveal the many different functions that this vast range of arts and artefacts served within the cultural and social context of the Eastern Mediterranean and Near East." "Combining the latest research and critical approaches with an up-to-date historiography this book gives readers a clear understanding of Ancient Aegean visual arts and of our changing interpretations of this extraordinary era."--Jacket.
-- Introduction : Aegean art and architecture -- The Neolithic Period and the Prepalatial Early Bronze Age -- The First Palace Period -- The Second Palace Period -- Mycenaean domination and the Minoan tradition -- Conclusion : disruptions, (dis)continuities, and the Bronze Age.
Includes bibliographical references (pages 232-240) and index.
Keywords: Art, Cretan -- History; Art, Aegean -- History; Crete (Greece) -- Antiquities